Relationships between green technological innovation, renewable energy, circular economy, and green growth - Afef Bouattour; Sarra Gharbi; Maha Kalai; Kamel Helali (Journal of Innovation & Knowledge (JIK), 2025)
This study employs the panel smooth threshold autoregression model to data spanning 27 European Union (EU) member states from 2000 to 2022 to investigate the nonlinear relationships between green growth and green technological innovation. This approach enables our examination of the dynamics of economies' rise from weakness to strength. This investigation introduces a comprehensive framework that combines green technological innovation, renewable energy sources, and the circular economy into a single green growth model. The results confirm two optimal thresholds that impact how green technological innovation affects green growth, distinguishing between the three regimes. Additionally, the results demonstrate the positive influence of green technological innovation on green growth. In contrast, the study reveals a weaker effect with increasing levels of green technological innovation transitions from intermediate (Regime 2) to high (Regime 3) green growth. Furthermore, insufficient green technological innovation has not developed effective renewable energy technologies that can foster green growth. Conversely, renewable energy begins to positively affect green growth when EU countries increase green technological innovation investment. Finally, a robust regime of green technological innovation facilitates circularity and promotes EU economies' green growth, indicating that the influence of the circular economy on green growth depends on increased green technological innovation. Practically, policymakers in EU economies should focus on sustainable innovation to promote green growth and advance the United Nations Sustainable Development Goals.
Keywords: G01; G21; M14; Q50; 650; 27 European Union countries; Circular economy; Green growth; Green technological innovation; Renewable energy